Telaah Filsafat Hukum terhadap Restorative Justice sebagai Upaya Dekonstruksi Paradigma Retributif dalam Sistem Pemidanaan di Indonesia - Mirza Athaya Ghaisan Hakeem; Aqiila Banyu Valentara; Achmad Faidzuddin; Muhammad Avin Athalla Rilya (Media Hukum Indonesia (MHI), 2026)
The development of criminal law in Indonesia shows a paradigm shift from a retributive to a restorative approach, particularly following the enactment of Law Number 1 of 2023 concerning the new Criminal Code (KUHP). This study aims to analyze the position of restorative justice as a mechanism to deconstruct the retributive paradigm and to evaluate its implementation in Indonesian criminal sentencing practices. The research uses normative legal methods with statutory and conceptual approaches, examining legal principles, frameworks, and relevant doctrines. The findings indicate that restorative justice plays a strategic role in shifting the focus of criminal law from mere punishment to victim restoration, offender accountability, and social reconciliation. Its application is supported by normative regulations and mediation practices involving victims, offenders, families, and communities, delivering substantive justice while reducing recidivism. Despite challenges such as varying interpretations among law enforcement officials and power imbalances between victims and offenders, restorative justice proves to be an effective mechanism for establishing a more humane, responsive, and just criminal justice system in Indonesia.